Edukasi Perilaku Hidup Sehat Tanpa Narkoba Pada SMP Nahdlatul Ulama (NU) Medan - Siti Nurlani Harahap; Fitri Dian Nila Sari; Saiful Amir; Nelfita Rizka S. Depari (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to provide education to students about the harmful effects of drugs on physical health, mental health, and their future; to build a school environment with an anti-drug culture that is safe. This community service activity was carried out at Nahdlatul Ulama (NU) Junior High School in Medan. The method of implementing community service consists of 3 stages are the preparation stage, the implementation stage, and the reporting stage. In the preparation stage, observations and identification of field problems. At the implementation stage, education about healthy lifestyle behaviors without drugs is provided to the students. At the reporting stage, which is the preparation of documents in the form of activity reports. The results of this PKM implementation can increase the knowledge, attitudes, and actions of participants regarding the dangers of drugs and how to carry out drug prevention efforts. This is proven through the comparison results between the pre-test and post-test, where there was an increase in the average knowledge score of counseling participants about types of drugs, the dangers of drugs, and efforts to prevent drug involvement from 71.05 to 83, The average attitude score of the participants also increased from 3.23 to 3.8, likewise the average Action score of the participants also increased from 0.87 to 0.88. The conclusions is there was a significant increase in the knowledge, understanding, attitudes, and actions of the participants after being given education about drugs.